2009
DOI: 10.1111/j.1365-313x.2009.03965.x
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the Arabidopsis mTERF‐related plastid protein SOLDAT10 activates retrograde signaling and suppresses 1O2‐induced cell death

Abstract: SUMMARYThe conditional flu mutant of Arabidopsis thaliana generates singlet oxygen ( 1 O 2 ) in plastids during a darkto-light shift. Seedlings of flu bleach and die, whereas mature plants stop growing and develop macroscopic necrotic lesions. Several suppressor mutants, dubbed singlet oxygen-linked death activator (soldat), were identified that abrogate 1 O 2 -mediated cell death of flu seedlings. One of the soldat mutations, soldat10, affects a gene encoding a plastid-localized protein related to the human m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(141 citation statements)
references
References 69 publications
3
138
0
Order By: Relevance
“…The Arabidopsis genome encodes 35 mTERF proteins, and GFP fusion studies suggested that 11 of these are plastid localized, 17 are localized to mitochondria, while the localization of the remaining seven has not been determined (Babiychuk et al, 2011). Several plastid-localized mTERF proteins (At4g02990, BSM; At2g03050, SOLDAT10; At2g21710, EMB2219; At4g02990, RUGOSA2) have been genetically characterized in Arabidopsis; the null mutants have pale-green or embryo-lethal phenotypes with defects in plastid gene expression, but the precise molecular functions are unclear (Tzafrir et al, 2004;Meskauskiene et al, 2009;Babiychuk et al, 2011;Quesada et al, 2011). We identified 10 mTERF proteins in the maize nucleoid samples; eight of these have Arabidopsis orthologs based on reciprocal BLAST analysis, all of which were shown to be chloroplast localized in GFP fusion assays (Babiychuk et al, 2011).…”
Section: Proteins Involved In Transcription and Rna Metabolismmentioning
confidence: 99%
“…The Arabidopsis genome encodes 35 mTERF proteins, and GFP fusion studies suggested that 11 of these are plastid localized, 17 are localized to mitochondria, while the localization of the remaining seven has not been determined (Babiychuk et al, 2011). Several plastid-localized mTERF proteins (At4g02990, BSM; At2g03050, SOLDAT10; At2g21710, EMB2219; At4g02990, RUGOSA2) have been genetically characterized in Arabidopsis; the null mutants have pale-green or embryo-lethal phenotypes with defects in plastid gene expression, but the precise molecular functions are unclear (Tzafrir et al, 2004;Meskauskiene et al, 2009;Babiychuk et al, 2011;Quesada et al, 2011). We identified 10 mTERF proteins in the maize nucleoid samples; eight of these have Arabidopsis orthologs based on reciprocal BLAST analysis, all of which were shown to be chloroplast localized in GFP fusion assays (Babiychuk et al, 2011).…”
Section: Proteins Involved In Transcription and Rna Metabolismmentioning
confidence: 99%
“…The importance of mTERF proteins in plants is demonstrated by their loss-of-function phenotypes. Arabidopsis mutants defective in the mTERF proteins SINGLET OXYGEN-LINKED DEATH ACTIVATOR10 (SOLDAT10)/ mTERF1 (Meskauskiene et al, 2009) and BELAYA SMERT (BSM)/RUGOSA2 (RUG2)/mTERF4 (Babiychuk et al, 2011;Quesada et al, 2011) exhibit developmental arrest in the embryo. The maize BSM ortholog ZmmTERF4 is responsible for group II intron splicing, and this function in chloroplast RNA splicing might be conserved in BSM/RUG2 (Hammani and Barkan, 2014).…”
mentioning
confidence: 99%
“…For example, several regulatory molecular components involved in 1 O 2 -mediated plastid-to-nucleus signaling have been identified through extensive genetic mutation screens in the background of the conditional flu mutant, such as EX1, EX2, SOLDAT10, PRL1, CAA33, CAA39 in Arabidopsis. [20][21][22][23][24][25] Two new plastid retrograde signals (PAP and MEcPP) during drought, high light and wounding stress responses have been revealed by two research teams, involving the analysis of the Arabidopsis mutants sal1 and ceh1, which encode the plastid nucleotidase/phosphatase SAL1 and hydroxyl-2-methyl-2-(E)-butenyl4-diphosphate synthase (HDS), respectively. 26,29 Analysis of the rps1 mutant demonstrated that the chloroplast ribosomal protein S1 (RPS1) mediates retrograde signaling to modulate the expression of the heat-responsive nuclear transcription factor HsfA2 and its target genes during heat stress, although the specific plastid retrograde signal is unknown.…”
Section: Molecular Components In Plastid Retrograde Signaling To Regumentioning
confidence: 99%
“…25 As an example of the fourth type, mutation of plastid SOLDAT10 disrupts chloroplast homeostasis by attenuating the decrease in plastid-specifc rRNA levels and protein synthesis, and affects the communication of 1 O 2 -mediated signaling between chloroplasts and the nucleus. 22 Similarly, mutation of plastid CAA33 disturbs chloroplast homeostasis by impeding plastid division, interfering with 1 O 2 -mediated plastid-to-nucleus signaling. 24 A further example can be seen in chloroplastic RPS1, involved in plastid protein translation and displaying a role in the synthesis of thylakoid membrane proteins we propose possible plastid retrograde signals for the AMOS1/ EGY1-dependent ammonium stress response (Fig.…”
Section: Interaction Of Plastid Retrograde Signaling and Aba Signalinmentioning
confidence: 99%
See 1 more Smart Citation